The World in the Post-Truth Era or How Too Much Love of TINA Will Kill You - Jarl K Kampen (The Central European Review of Economics and Management (CEREM), 2017)
Aim: ~The temptation to provide simple answers to complex problems exists for politicians and scientists alike. This essay attempts to briefly outline the complexity of present day problems at global level, taking as a starting point the question "how quick will the EU collapse?"~Design / Research methods:~Brief discussions are given of separate yet interconnected, causally related and overlapping natural and social research domains, illustrating the need for qualified multidisciplinary spokesmen able to separate facts from "alternative facts."Conclusions / findings:~ Making the simple anthropological observation that people can choose policies that are self-destructive does not make social science politicized or value-biased. A society that considers global warming, depletion and pollution caused by fossil fuels as mere externalities makes a demonstrable erratic choice. Because one of the major goals of science is to establish (in)validity of "common sense," it is duty of academics to tell our students that societies, including entire scientific departments, can make consistent erratic choices.Originality / value of the article:~This essay may help scholars and practitioners to start to look at their research domain in a (much) wider global context. – – Cel: Zaroẃno politycy, jak i naukowcy zmagaja sie z pokusa, aby udzielacṕrostych odpowiedzi naskomplikowane pytania. W artykule tym podjeto prob́e zwiezłego zarysowania dzisiejszychproblemoẃ na poziomie globalnym, a jako punkt startowy przyjeto pytanie: "Jak szybko upadnie UniaEuropejska?".Układ / metody badawcze: Natura tematyki wskazuje raczej na holistyczne podejsćie interpretacyjneanizėli na systematyczne podejsćie redukcjonistyczne. Przedstawiono krot́kie dyskusje dotyczaceoddzielnych, aczkolwiek powiazanych wzajemnie i nachodzacych na siebie naturalnych i społecznychdomen badawczych, ilustrujace potrzebe wykwalifikowanych multidyscyplinarnych moẃcoẃ,zdolnych rozroźṅiacf́akty od "alternatywnych faktoẃ".Wnioski / wyniki: Zwykłe antropologiczne obserwacje, zgodnie z ktoŕymi ludzie sa w stanie wybracṕolityke polegajaca na samodestrukcji, niekoniecznie czynia nauki społeczne upolitycznionymi badzńastawionymi na wartosć\'. Społeczenśtwo uznajace globalne ocieplenie, wyczerpywanie sie izanieczyszczenia spowodowane przez paliwa kopalne za zaledwie efekty zewnetrzne, dokonujedemonstracyjnego nieobliczalnego wyboru. Poniewazj̇ednym z podstawowych celoẃ nauki jestustalenie (nie)zasadnosći "wspoĺnego sensu", akademicy maja obowiazek moẃienia studentom, zėspołeczenśtwa, właczajac całe sŕodowiska naukowe, moga dokonywacćiagłych nieodpowiedzialnychwyboroẃ.Oryginalnosć\' / wartosćártykułu: Artykuł mozė wspomoć naukowcoẃ i praktykoẃ w rozpoczeciuspogladania na ich obszary badawcze w (o wiele) głebszym globalnym konteksćie.
Keywords: P10; P28; P36; Q20; Q40; Q50; 330; TINA; multidisciplinary research; climate change; governance